The Conformity of Social Responsibility in Terms of Islamic Social Reporting Index (ISR) among Islamic Banks in Indonesia - Filianti, Dian; Septiarini, Dina Fitrisia (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the compatibility of disclosure in social responsibility by adopting Islamic Social Reporting (ISR) for the Islamic banks in Indonesia. This research adopted the descriptive analysis in the qualitative approach and used content analysis technique. Sampling method is purposive sampling. There are 13 Islamic banks in Indonesia that are the object of research. Data used is secondary data of the annual reports of total 13 Islamic banks in 2016-2018 were downloaded from the banks official website. The findings of this research indicated that Islamic banks in Indonesia able to disclose the compatibility of social disclosure but not full disclosure yet. Furthermore, the results revealed that 15% of Islamic banks are not compatible with disclosure in social responsibility and 33% of categories are not compatible with Islamic Social Reporting (ISR), which are labour and environment section.